2019
DOI: 10.1108/ijbpa-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Housing attributes and relative house prices in Ghana

Abstract: Purpose The study of house prices has become more relevant in recent times after the global financial crisis. Using a housing data set from three regions of Ghana (collated from real estate agents), the purpose of this paper is to estimate the relative importance of housing attributes to house prices. Design/methodology/approach The hedonic regression analysis conducted indicates that location is the most powerful determinant of house prices. Other relevant factors are the number of bedrooms, the number of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…According to [13], efficiency of public education, community social status and proximity to shopping malls typically improve the worth of a property. There is a substantial rise in house prices from the fifth-class suburban community to affluent neighborhood as predicted [16]. Nonetheless, [13] study found that these qualities tend to be cultural based, as they are not similarly relevant in all cultures.…”
Section: Neighbourhoodmentioning
confidence: 87%
See 2 more Smart Citations
“…According to [13], efficiency of public education, community social status and proximity to shopping malls typically improve the worth of a property. There is a substantial rise in house prices from the fifth-class suburban community to affluent neighborhood as predicted [16]. Nonetheless, [13] study found that these qualities tend to be cultural based, as they are not similarly relevant in all cultures.…”
Section: Neighbourhoodmentioning
confidence: 87%
“…In [14] in his earlier study, structural attributes would be the key consideration for house hunters in determining what to purchase as such attributes represent their market value. In their earlier study, [15] stated that all these attributes have a positive relationship to rising house prices [16].…”
Section: B Structuralmentioning
confidence: 99%
See 1 more Smart Citation
“…Edwards et al , 1998; Burton et al , 2021; Posillico et al , 2021), which revealed that a quantitative research strategy was commonly used in previous similar studies (cf. Owusu-Manu et al , 2019; Spellacy et al , 2020; Owusu-Manu et al , 2021). Deductive reasoning (cf.…”
Section: Research Frameworkmentioning
confidence: 99%
“…Technical condition, often represented by age, is a significant price-setting factor in several research studies. However, the method of evaluating a specific condition is not usually described (Ventolo and Williams, 2005; Owusu-Manu et al , 2019; Rong and Sun, 2014; Ooi et al , 2014). Based on the market knowledge, a large number of sold houses were built in the past and repeatedly renovated and rebuilt.…”
Section: Introductionmentioning
confidence: 99%